1994
DOI: 10.1111/j.1365-2796.1994.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant hepatitis with severe lactate acidosis in HIV‐infected patients on didanosine therapy

Abstract: We report two cases of fulminant hepatic failure in HIV-1-infected patients treated with didanosine (ddI). Clinical manifestations including vomiting, diarrhoea and dyspnoea were identical in both cases. Biological data mainly revealed hepatic failure and lactic acidosis. Histological examination of liver biopsies showed diffuse microvesicular steatosis. The outcome was fatal in both patients. The only comparable case previously reported (Lai et al., 1991) showed close similarities in the clinical, biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 15 publications
2
70
0
Order By: Relevance
“…5,6 Hepatic steatosis, lactic acidosis, and ultrastructural abnormalities of mitochondria were similar to those of Reye' s syndrome, in which mitochondrial injury is believed to be a critical factor in pathogenesis. 20,21 Hepatic steatosis and lactic acidosis have been observed in patients treated with other nucleoside analogs including ddC, 22 ddl, 23,24 and AZT, [25][26][27] and multiorgan involvement similar to that associated with FIAU toxicity has been attributed to nucleoside-induced mitochondrial damage. 10,28 The mechanism(s) responsible for FIAU-induced mitochondrial dysfunction and the role of mitochondrial dysfunction in FIAU toxicity are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Hepatic steatosis, lactic acidosis, and ultrastructural abnormalities of mitochondria were similar to those of Reye' s syndrome, in which mitochondrial injury is believed to be a critical factor in pathogenesis. 20,21 Hepatic steatosis and lactic acidosis have been observed in patients treated with other nucleoside analogs including ddC, 22 ddl, 23,24 and AZT, [25][26][27] and multiorgan involvement similar to that associated with FIAU toxicity has been attributed to nucleoside-induced mitochondrial damage. 10,28 The mechanism(s) responsible for FIAU-induced mitochondrial dysfunction and the role of mitochondrial dysfunction in FIAU toxicity are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome has also been reported in patients receiving other antiretroviral nucleoside analogue therapy, including retrovir (AZT) and didanosine (ddI) but in a more reversible form. 36 In vitro and in vivo systems have been devised for assessing mitochondrial injury. These tests include incubation of hepatocyte cultures (primary or transformed) with drug and quantitation of mitochondrial morphology, DNA content, respiratory chain enzymes, and lactate production.…”
Section: J H Hoofnagle B C Tennant W Lewis and R J Sokolmentioning
confidence: 99%
“…In vivo assessment of mitochondrial toxicity of metacavir in Rhesus monkeys after three months of intravenous administration 1667 www.chinaphar.com Zeng W et al Acta Pharmacologica Sinica npg zalcitabine (ddC), didanosine (ddI) and stavudine (d4T) [14][15][16] . A study of maternal-fetal exposure to AZT in patas monkeys also showed evidence for mitochondrial dysfunction including respiratory-chain defects and mtDNA reduction [17] .…”
Section: Introductionmentioning
confidence: 99%